Scrounging, a cookbook 54 recipes for midnight and the morning after, detention and the apocalypse, and other dire situations - Drumm, Perrin; Rhodes, Margaret (A24 Films, 2023)
A theory of scrounging -- Beverages -- Breakfast -- Appetizers and snacks -- Sandwiches -- Dinner -- Dessert
"Meals as seen in 17 Again, The Apartment, Betty Blue, The Breakfast Club, Cool As Ice, Home Alone, Kramer vs. Kramer, O Brother, Where Art Thou?, Phantom Thread, Step Brothers, To Sir, With Love, Waiting For Guffman, War Of The Worlds, and more..." -- title page
Keywords: Food in popular culture; cookbooks; recipes; Cookbooks; Recipes; Livres de cuisine; Recettes; Kochbuch